Judicial Neutrality in Corruption Trials: A Contemporary Islamic Law Perspective on Independence in Transitional Legal Systems - Irman Syahriar; Indera Dewi; Fifi Loanardy; Jamil Khairunnisah; Bilal Hussain (Faculty of Sharia, IAIN Metro, 2025)
This study examines the dynamics of judicial neutrality in corruption trials within transitional legal systems, analysed through the lens of Contemporary Islamic Law. The research aims to investigate how political pressures, systemic weaknesses, and legal culture affect judicial independence, and to evaluate the alignment of judicial conduct with the ethical and procedural principles embedded in Islamic legal thought. Employing a qualitative legal research method that draws on statutory, case, and conceptual approaches, the study synthesises legal texts, judicial decisions, and scholarly commentaries. The findings reveal that in transitional legal systems, judicial neutrality is often compromised by political interference, inadequate institutional safeguards, and cultural tolerances toward corruption, resulting in a crisis of public trust. From the perspective of Contemporary Islamic Law, the preservation of judicial independence is not only a procedural requirement but also a moral imperative grounded in maqāṣid al-sharī‘ah, particularly the protection of justice (ḥifẓ al-‘adl) and public interest (maṣlaḥah' āmmah). The study concludes that integrating Contemporary Islamic legal principles into anti-corruption judicial reforms can strengthen institutional independence, reinforce ethical accountability, and restore public confidence in the judiciary. This research contributes academically by bridging the discourse between legal reform in transitional contexts and the evolving application of Islamic legal theory to contemporary governance challenges.